Thinking Non Locally: The Atemporal Roots of Particle Physics - Chiatti, Leonardo (Frontiers in Physics, 2018)
Developing an approach defined in previous papers a correspondence between elementary particles and elements of a particular set of directed graphs said “glyphs” is made explicit. These can, in turn, be put in correspondence with a particular set of biquaternions. Charge conjugation and weak isospin inversion then become both topological (on glyphs) and algebraic (on biquaternions) symmetries. The formalism describes leptons and quarks, the latter successfully combined into mesons and baryons. The introduction is possible of both a de Sitter interior spacetime of particles and the usual external Minkowski spacetime. The biquaternions can be related to creation and annihilation operators of the corresponding fermionic fields in Quantum Field Theory (QFT). The base states of QFT and their mutual interactions are thus constrained by their common emergence from logically antecedent structures. This result appears relevant for the understanding of the elementary particles spectrum.